Gambaran Pemberdayaan Masyarakat Peduli Api (MPA) di Kelurahan Kereng Bangkirai dan Sabaru Kota Palangka Raya Kalimantan Tengah - Pamela Dewi Widuri; Mochammad Bagus Qomaruddin; Rachmat Hargono (Media Gizi Kesmas, 2023)
Background: The form of community empowerment that can support in tackling cases of forest and land fires is the Fire Care Community (MPA), namely communities in areas prone to forest and land fires who voluntarily care about controlling forest and land fires who have been trained or given supplies and can be empowered to assist forest and land fire control activities Objective: To know the general description of the empowerment of the Fire Care Community (MPA) in preparedness efforts in Kereng Bangkirai and Sabaru Villages, Palangka Raya City, Central Kalimantan Methods: This research was qualitative research with a case study design. Data collection techniques used are in-depth interviews and FGDs. This study used a case study approach to explore and obtain in-depth information to explore the perspectives of MPA members and related communities. Results: Kelurahan Kereng Bangkirai and Sabaru in carrying out their roles had met expectations. At the beginning, the performance of MPA Kereng Bangkirai was considered very good compared to MPA Sabaru because members of MPA Kereng Bangkirai were quite vocal and active. Still, over time there were internal problems in MPA Kereng Bangkirai which affected the performance of MPA Kereng Bangkirai team. The situation turned around, now MPA Sabaru was considered to have better performance because of the activeness and cohesiveness of the MPA Sabaru team. Conclusion: The empowerment of MPA in Kereng Bangkirai and Sabaru Villages has been quite good in carrying out their roles, but along the way, both MPA in Kereng Bangkirai and Sabaru Villages have had several obstacles, both internal and external.